KEANEKARAGAMAN BURUNG DI KAWASAN MANGROVE KOTA BANDA ACEH - Ahadi, Rizky; Zuraidah, Zuraidah; Ernilasari, Ernilasari (KENANGA : Journal of Biological Sciences and Applied Biology, 2024)
Birds, as natural inhabitants of mangrove areas, play an important role in maintaining the stability of the ecosystem and its components. This research aims to determine the species diversity index of birds in the mangrove ecosystem of Banda Aceh City. The method used is an exploratory survey, conducting direct observations at each research location using purposive sampling. Field data collection was carried out in May 2022. Birds diversity data were analyzed using the Shannon-Wiener Index. The results identified 17 bird species from 11 families, with the birds species diversity index in the mangrove ecosystem of Banda Aceh City falling into the moderate category (H’ = 1.99). These findings indicate that the mangrove ecosystem in Banda Aceh has significant potential in supporting biodiversity, which is crucial for further management and conservation efforts.